THE IMPACT OF LASALLIAN HEALTH EDUCATION ON IMPROVING WOMEN BEHAVIOR WITH HIGH CHOLESTEROL LEVELS - Isaura Isabela Lontaan; Annastasia S. Lamonge; Indriani Yauri (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: High cholesterol is one of the causes of coronary heart disease and stroke. Diet and activity patterns are the two main factors that can lead to high cholesterol levels in the blood. Therefore, it needs good knowledge, skills, and motivation that is strong enough, to be able to effectively prevent high cholesterol occurrence. The purpose of this study is to identify the effectiveness of Lasallian health education on improving women's behavior with high cholesterol levels in the village Poigar II South Minahasa regency. Methods. The research design is a Quasi Experiment using Pre Test Post Test Design with Control Group. The numbers of participants were 32 people with a purposive sampling technique of sampling. Data were collected by questionnaires and analyzed using the Wilcoxon test and Mann Whitney tests. Results. Research shows the effect of Lasallian health education on improving women's behavior with high cholesterol levels with significant values p-Value = 0.001 (p-value < α 0.05). Discussion: This method can help respondents to open up and share experiences so that sharing can be a motivation for each respondent in terms of changing behavior for the better. If there is a good experience that was told by the respondent that can be done, it can be taken and if the experience about the bad behavior can be issued. Conclusion: It can be concluded that there is an effect of Lasallian health education on the improvement of women 's behavior. So that the advice given in this study is so this can be useful for the society, especially women patients to be able to acquire the knowledge, skills, and motivation.